Mapping trends and knowledge structure of energy efficiency research: What we know and where we are going - Mahi, Masnun (Springer Heidelberg, 2021)
Energy efficiency (EE) is an evolving research aspect for researchers, businesses, and policymakers for its undeniable role in meeting increasing energy demand, reducing CO2 emissions, and tackling climate change. This paper provides a review of the current state of EE research by mapping the research landscape in business and economics to understand the socioeconomic dimensions within these research areas. To identify key information, we examine the trends and characteristics of 2935 relevant scientific publications over a 30-year period from 1990 to 2019 in the Social Science Citation Index of the Web of Science database using bibliometric analysis with a R language package called `bibliometrix'. Our analysis shows an increasing trend in publications from 2006 onwards; the period remarkably coincides with the implementation phase of the Kyoto protocol in 2005. Accordingly, we observe that EE research has a strong association with issues like CO2 emissions, climate change, sustainability, and the growing importance of these issues in recent years. Thus, our findings provide crucial understandings by incorporating a wide array of scientific outputs in response to calls for greater theoretical clarification of EE research. These findings provide insights into the current state of the art of, and identify crucial areas for future, research. Hence, our research assists in formulating environmentally sustainable policies to tackle the adverse effects of CO2 emissions and related climate change through providing critical grasps on the scholarly development related to EE.